2019
DOI: 10.1002/lary.27859
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in nasal obstruction and quality of life after septorhinoplasty and turbinate surgery

Abstract: Objectives: To evaluate the long-term impact of functional septorhinoplasty (SRP) with and without inferior turbinate reduction (ITR) on disease-specific symptom severity and general health-related quality of life (QOL).Study Design: Prospective cohort study at a tertiary referral center. Methods: Patients undergoing functional SRP with and without ITR were administered the Nasal Obstruction Symptom Evaluation (NOSE) scale to assess severity of nasal obstruction and the EuroQol-5 Dimension Questionnaire Visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 33 publications
5
26
0
Order By: Relevance
“…We note a greater mean improvement in 12-month postoperative SOS when ITR is performed, although further studies are needed to fully characterize incremental differences in SDB-related outcomes for specific anatomic causes of nasal obstruction and the numerous combinations of rhinoplasty and nasal surgery techniques that can be performed to address obstructive anatomy. 34 There are no widely recognized predictive measures that link the site of nasal obstruction to the degree of snoring improvement that patients may expect after surgery. Our finding that 62.3% of SDB patients had a clinically significant improvement in snoring symptoms at 12 months may be used as a reference to approximate the number of patients who may experience postoperative improvement in snoringrelated QOL.…”
Section: Snoring Outcomes After Septorhinoplasty 29mentioning
confidence: 99%
“…We note a greater mean improvement in 12-month postoperative SOS when ITR is performed, although further studies are needed to fully characterize incremental differences in SDB-related outcomes for specific anatomic causes of nasal obstruction and the numerous combinations of rhinoplasty and nasal surgery techniques that can be performed to address obstructive anatomy. 34 There are no widely recognized predictive measures that link the site of nasal obstruction to the degree of snoring improvement that patients may expect after surgery. Our finding that 62.3% of SDB patients had a clinically significant improvement in snoring symptoms at 12 months may be used as a reference to approximate the number of patients who may experience postoperative improvement in snoringrelated QOL.…”
Section: Snoring Outcomes After Septorhinoplasty 29mentioning
confidence: 99%
“…Nevertheless, when a patient has NSD accompanied by chronic nasal obstruction, NSD is considered as a disease. Nasal obstruction is the most common complaint, seriously affecting the patient's quality of life [3,4]. In fact, an NSD is the most common cause of nasal obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…The inferior turbinoplasty is considered to be another important aspect of nasal ventilation surgery except for septoplasty due to the significant role of IT in the physiology of nasal ventilation and the pathology of nasal obstruction [19]. Recently, compensatory hypertrophy of IT second to NSD has turned to be another significant issue [20,21] and it has been proposed that the turbinate reduction surgery should be conducted along with septoplasty [4,[20][21][22]. However, a study by van Egmond et al [8] showed no clinical differences between septoplasty alone and septoplasty with concurrent turbinate surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 A variety of treatment strategies, both surgical and nonsurgical, have been used with success in improving nasal obstruction and quality of life. [6][7][8] Surgical treatments include septoplasty, turbinate reduction, and functional rhinoplasty with repair of nasal valve stenosis. Nasal steroids and saline irrigation are among the more common medical treatment strategies.…”
mentioning
confidence: 99%